2022
DOI: 10.3389/fpsyg.2022.813529
|View full text |Cite
|
Sign up to set email alerts
|

Do Self-Regulated Learning Practices and Intervention Mitigate the Impact of Academic Challenges and COVID-19 Distress on Academic Performance During Online Learning?

Abstract: The COVID-19 pandemic introduced significant disruptions and challenges to the learning environment for many post-secondary students with many shifting entirely to remote online learning. Barriers to academic success already experienced in traditional face-to-face classes may be compounded in the online environment and exacerbated by stressors related to the pandemic. In 2020–2021, post-secondary institutions were faced with the reality of rolling out fully online instruction with limited access to resources f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…E-learning in higher education was boosted by the Covid-19 pandemic, which led to severe changes in study conditions and student learning. Although e-learning offers students more flexibility and saves them travel times, it is associated with higher demands in terms of self-regulation skills and characterized by less social integration ( Broadbent & Poon, 2015 ; Goppert & Pfost, 2021 ; Hadwin et al, 2022 ). Social embeddedness and interactions are crucial for motivation and retention in studies (e.g., Broadbent & Poon, 2015 ).…”
Section: E-learning and Ert In German Higher Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…E-learning in higher education was boosted by the Covid-19 pandemic, which led to severe changes in study conditions and student learning. Although e-learning offers students more flexibility and saves them travel times, it is associated with higher demands in terms of self-regulation skills and characterized by less social integration ( Broadbent & Poon, 2015 ; Goppert & Pfost, 2021 ; Hadwin et al, 2022 ). Social embeddedness and interactions are crucial for motivation and retention in studies (e.g., Broadbent & Poon, 2015 ).…”
Section: E-learning and Ert In German Higher Educationmentioning
confidence: 99%
“…Studying is associated with increased stress ( Matos Fialho et al, 2021 ; von Keyserlingk et al, 2021 ) even without additional stressors due to the changes brought by the Covid-19 pandemic. With reference to prior findings on the development of stress or students' perception of e-learning ( Garrison et al, 2010 ; Schmidt et al, 2019 ), social presence and cognitive abilities are crucial for the evaluation of the learning process and the motivation in digital learning environments ( Kahn et al, 2017 ) and ERT ( Hadwin et al, 2022 ; Hopp et al, 2021 ). Previous studies revealed core conditions for the development of distress in e-learning: limited opportunities for action (e.g., due to technical difficulties and low support; Hara, 2000 ), reduced social interactions with peers, lecturers, and tutors ( Garrison et al, 2010 ; Henritius et al, 2019 ; Hopp et al, 2021 ), and an increased need to control the learning process by oneself ( Hadwin et al, 2022 ).…”
Section: Stress In Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations